THE APPLICATION OF ELECTRONIC MEDICAL RECORDS IN HOSPITALS: A GENERAL OVERVIEW - Nik Azliza Nik Ariffin; Jannatul Iza Ahmad Kamal; Dr.Alwi Mohd Yunus; Dr.Syamsuriansyah; Dr. Irwan Kamaruddin Abdul Kadir (Journal of Islamic, Social, Economics and Development, 2023)
As hospitals switch from traditional processes to electronic recordkeeping, the use of health information systems is expanding quickly. Health information systems are cutting-edge products designed to improve effective healthcare delivery. Electronic medical record (EMR) system adoption comes with a long list of benefits, including better patient care, higher-quality paperwork, and better record-keeping, but there have also been unanticipated side effects. Inadequate EMR system design and excessive complexity can result in EMR-related errors that endanger the privacy, confidentiality, and security of the data in the EMR, creating a significant backlog in converting older paper medical records to electronic format, incurring high costs, and depriving end users of IT skills. These unexpected dangers could also encourage hoaxes and improper handling, which would have major legal repercussions. This study aims to examine any potential dangers or problems that can arise from using electronic medical records in hospitals. EMR systems pose risks to patient care, which are examined in this literature review along with suggested remedies for EMR-related mistakes. This review of the literature on EMR risks aims to stimulate further investigation into these potential risks, their implications for patient safety and care quality, and possible mitigation measures.